INVENTARISASI “RUMAH GADANG” SEBAGAI SIMBOL BUDAYA (Pemberdayaan bidang kebudayaan di Nagari Pasie Laweh) - Irwandi Irwandi; Romi Maimora (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2021)
Nagari Pasie Laweh has considerable potential, both human resources potential, natural resources (SDA) potential, as well as artistic, traditional and cultural potential. One of the potentials that need to be preserved is the potential that symbolizes culture. Based on this, in order to preserve the cultural symbols, it is necessary to take comprehensive steps from stakeholders, including by conducting an inventory. The inventory is carried out using a qualitative research method with a descriptive approach. From the results of the implementation of the inventory, the following results were obtained, including the number of remaining rumah gadang in nagari pasie laweh totaling 30 units with the following conditions; a. good condition and can be occupied, b. good condition but not occupied, c. unfavorable condition but can be occupied, d. poor condition and cannot be occupied. Responding to this and addressing the problem of cultural symbols in the Pasie Laweh village, special attention is needed from the Nagari government and the Nagari Customary Density (KAN) Nagari.